Teaching Chinese literacy in the early years psychology, pedagogy and practice - Li, Hui 1968- (Routledge, 2015)
"The Chinese language is now used by a quarter of the worlds population and is increasingly popular as a second language. Teaching Chinese Literacy in the Early Years comprehensively investigates the psychology, pedagogy and practice involved in teaching Chinese literacy to young children. This text not only explores the psycholinguistic and neuropsychological processing involved in learning Chinese literacy but also introduces useful teaching methods and effective practices relevant for teaching within early years and primary education.Key issues explored within this text include:The Psycholinguistics of Chinese Literacy Neuropsychological Understanding of Chinese LiteracyThe pedagogy of teaching Chinese as a first languageThe Pedagogy of Teaching Chinese as a second language Teaching Chinese literacy in early childhood settingsAssessing Chinese Literacy Attainment in the Early YearsWith the addition of two reliable Chinese literacy scales, Teaching Chinese Literacy in the Early Years is an essential text for any student, lecturer or professional teacher who is interested in learning and teaching Chinese literacy. "..
Keywords: FOREIGN LANGUAGE STUDY / Chinese; LANGUAGE ARTS & DISCIPLINES / Literacy; EDUCATION / Preschool & Kindergarten; Psychologie; Chinese language -- Study and teaching (Primary) -- China; Chinese language -- Spoken Chinese -- Study and teaching (Primary) -- China; Chinese language -- Psychological aspects; Literacy -- China; Second language acquisition -- China; Ausländer; Chinesischunterricht; Kind; Psycholinguistik